Marriage Anxiety among Generation Z and Millennials: An Islamic Family Law Perspective - Siti Sahnia Mammenasa Daeng Yusuf; Hendri Sayuti; Siti Yulia Makkininnawa (JURNAL ISLAM NUSANTARA, 2025)
This study investigates the phenomenon of marriage anxiety among Generation Z and Millennials in Indonesia. This concern has become increasingly relevant amid modern social, cultural, and religious shifts. The research aims to understand the factors influencing young people’s perceptions of marriage, including economic instability, digital media influence, and evolving gender roles, and to propose a reinterpretation of Islamic family law to address contemporary concerns. Findings reveal that financial pressures, lack of religious education, societal expectations, and the influence of social media contribute significantly to the fear of marriage. Additionally, the study highlights the need for a more flexible and equitable approach to marital readiness, with a focus on emotional, social, and financial preparedness. Employing a normative qualitative research method, the study combines sociological and Islamic legal perspectives to offer a comprehensive understanding of marriage anxiety. The research concludes that addressing these fears through a blend of cultural, religious, and socioeconomic support can foster healthier perceptions of marriage and promote its value in modern society. The study contributes to the renewal of marriage concepts, ensuring their relevance in contemporary Indonesia.